2022
DOI: 10.1109/tmi.2022.3199498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Matrix Imaging—Part I: The Focused Reflection Matrix, the F-Factor and the Role of Multiple Scattering

Abstract: This is the first article in a series of two dealing with a matrix approach for aberration quantification and correction in ultrasound imaging. Advanced synthetic beamforming relies on a double focusing operation at transmission and reception on each point of the medium. Ultrasound matrix imaging (UMI) consists in decoupling the location of these transmitted and received focal spots. The response between those virtual transducers form the so-called focused reflection matrix that actually contains much more inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…We first suppose that 𝑎 Tx/Rx , ℎ Tx/Rx , and Δ𝜏 Tx/Rx vary slowly in the medium and thus can be assumed constant in V(𝒓 w ) and equal to their value at 𝒓 w . Practically, V(𝒓 w ) is equivalent to the isoplanatic patch used in [20], [23]. Moreover, we introduce a local Rx angle…”
Section: B Local Angular Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We first suppose that 𝑎 Tx/Rx , ℎ Tx/Rx , and Δ𝜏 Tx/Rx vary slowly in the medium and thus can be assumed constant in V(𝒓 w ) and equal to their value at 𝒓 w . Practically, V(𝒓 w ) is equivalent to the isoplanatic patch used in [20], [23]. Moreover, we introduce a local Rx angle…”
Section: B Local Angular Frameworkmentioning
confidence: 99%
“…Once a single sinogram 𝑓 per window position is obtained using Algorithm 1, we recover the estimations of the corresponding local patches by applying the backprojection operator R * to 𝑓 𝛾 f, p 𝒓 ′ , 𝒓 w = ∫ 𝜃 𝑓 𝜃, 𝒖(𝜃), 𝒓 ′ − 𝒓 w , 𝒓 w d𝜃, (23) in the continuous domain. Backprojection is then repeated for each window position 𝒓 w 𝑝,𝑞 .…”
Section: E Image Reconstructionmentioning
confidence: 99%
“…To express this quantity theoretically, we first make a local isoplanatic approximation in the vicinity of each point prefixfalse(ρmtrue,zpostfixfalse) $({\boldsymbol{\rho }}_{m},z)$ (Lambert, Robin, et al., 2022). Isoplanicity means here that waves which focus in this region are assumed to have traveled through approximately the same areas of the medium, thereby undergoing identical phase distortions.…”
Section: Passive Seismic Matrix Imagingmentioning
confidence: 99%
“…As opposed to methods that model the phase aberration effect by a fixed near-field phase screen in front of the transducer, the locally adaptive phase aberration correction technique [14] assumed a spatially varying near-field phase screen and employed multistatic synthetic aperture data to perform the correction at each point adaptively. Lambert et al suggested compensating for the spatially-distributed aberrations by decoupling aberrations undergone by the outgoing and incoming waves utilizing the distortion matrix built from the focused reflection matrix, which contains the responses between virtual transducers synthesized from the transmitted and received focal spots [15], [16], [17].…”
Section: A Related Workmentioning
confidence: 99%
“…It should be noted that due to the numerical precision of simulations in Field II, the initial sampling frequency was set to 104. 16 MHz, and the simulated data was later downsampled by a factor of 5. All images were simulated using a full synthetic aperture scan, followed by the synthesis of plane-wave images with 384 columns from the acquired data and saved as RF data.…”
Section: B Phase Aberration Implementationmentioning
confidence: 99%